Masculinities in the fiction of Pan Yutong and Li Tianbao - Ho, Kee Tee (2013)
Pan Yutong and Li Tianbao are both well-known Mahua fictionists. Due to the gorgeous writing style and the consideration about female, their works of fiction are always being seen as having femininities. Thus, the writings of masculinity in their fictions are worth to be explored. This study applies R.W. Connell’s Theory of Masculinities Practice in analysing the construction of masculinities amongst these fictions which were presented or shown by the male characters in different circumstances. This research found out that, male who applies the hegemony of masculinity would dominate female by using male’s privilege, physical strength and economic superiority. This phenomenon is also reflecting the relationship between males and patriarchy, as well as the oppression of female. Through the study of complicity of masculinity, there are two issues could be explained: the reason that female is willing to be dominated by men and the desire of male to dominate female. The group of man that lack of domination towards women will be seen as subordination of masculinity and being discriminated by men in general. Li Tianbao is used to the depiction of this type of male characters in his works of fiction. In which the men were being exploited because of the difference of working classes and races, they are considered as practitioners of marginalisation of masculinity. In the other hand, Pan Yutong tends to depict the way these men construct their masculinities in the adversity of life. As a conclusion, this study points out that, although Pan Yutong and Li Tianbao include femininities in their fictions, masculinities which identifies to patriarchy could be seen clearly in fictions.